m + 9 là ước số của 9m + 68
=> 9m + 68 chia hết cho m + 9
=> 9m + 81 - 13 chia hết cho m + 9
=> 9( m + 9 ) - 13 chia hết cho m + 9
Vì 9( m + 9 ) chia hết cho m + 9
=> 13 chia hết cho m + 9
=> m + 9 ∈ Ư(13) = { ±1 ; ±13 } ( bạn tự làm tiếp :)) )
Trả lời:
Ta có \(m+9\inƯ\left(9m+68\right)\)
Hay \(9m+68⋮\left(m+9\right)\)
\(\Leftrightarrow9\left(m+9\right)-13⋮\left(m+9\right)\)
\(\Rightarrow\left(m+9\right)\inƯ\left(13\right)=\left\{\pm1;\pm13\right\}\)
Ta có bảng sau:
m+9 | 1 | -1 | 13 | -13 |
m | -8 | -10 | 4 | -22 |
Vậy \(x\in\left\{-8;-10;4;-22\right\}\)thì \(m+9\inƯ\left(9m+68\right)\)
:)) cảm ơn mn nhiều!